2007
DOI: 10.1097/pec.0b013e3180328c92
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Intranasal Midazolam for the Treatment of Pediatric Seizures

Abstract: The IN-MAD midazolam controlled seizures better than PR diazepam in the prehospital setting and resulted in fewer respiratory complications and fewer admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 24 publications
0
93
0
4
Order By: Relevance
“…21 In addition to the aforementioned advantages from Bhattacharyya et al, 40 the investigators demonstrated that midalozam-treated patients were less likely to be seizing on presentation to the emergency department, needed less additional seizure medication, had a lower incidence of intubation, or were less likely to be admitted to the hospital or intensive care unit.…”
Section: Experience With Intranasal Delivery Of Benzodiazepines For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition to the aforementioned advantages from Bhattacharyya et al, 40 the investigators demonstrated that midalozam-treated patients were less likely to be seizing on presentation to the emergency department, needed less additional seizure medication, had a lower incidence of intubation, or were less likely to be admitted to the hospital or intensive care unit.…”
Section: Experience With Intranasal Delivery Of Benzodiazepines For Tmentioning
confidence: 99%
“…13 Increased nasal mucus production is commonly observed with actively seizing patients and could be clinically relevant to intranasal drug administration for treatment of seizures. Holsti et al 21 recognized this consideration in their pre-hospital treatment protocol that called for suction of mucus from the nasal cavity prior to administration of intranasal midazolam. Pre-treatment nasal cavity suctioning was likely contributory to the success observed in rapidly aborting seizure activity after intranasal midazolam administration.…”
Section: Nasal Anatomy As Related To Intranasal Drug Deliverymentioning
confidence: 99%
“…Of those 13 (Table). 1,8,12,13 Bhattacharyya and colleagues 12 compared intranasal midazolam to rectal diazepam in 46 children who presented to the ED with febrile or afebrile seizures. Baseline characteristics were similar between the 2 groups.…”
Section: Time To Seizure Cessationmentioning
confidence: 99%
“…Prospective and retrospective evidence shows that intranasal midazolam terminates seizures at least as fast as rectal diazepam. 1,5,8,[12][13][14][15] Most clinical studies have used a 5 mg/mL midazolam solution dosed at 0.2 mg/ kg (divided into each nostril) administered via an intranasal mucosal atomization (IN-MADD) device or nasal dropper as suggested by Kyrkou and colleagues. 16 Three open-labeled studies prospectively evaluated the time to seizure cessation with a dose of nasal midazolam (Table).…”
Section: Time To Seizure Cessationmentioning
confidence: 99%
See 1 more Smart Citation